Pengaruh Sikap, Pendidikan dan Lingkungan Sosila terhadap Intensi Berwirausaha - Puspaningrum, Klara Gendis; Margunani, Margunani (Universitas Negeri Semarang, 2021)
This study aims to influence attitudes, education and social environment on entrepreneurial intentions. The population in this study was class XII students of SMK PL Accounting & Finance Institution 1 and XII Office Automation & Governance 1 taken from the number of students of SMK PL Tarcisius 1 Semarang in the 2019/2020 academic year totaling 170 people and saturated samples were taken. Data were collected by questionnaire. Data were analyzed by descriptive analysis and multiple linear regression analysis. The results showed that (1) attitudes, education, and social environment had a simultaneous effect on entrepreneurial intentions, (2) attitudes had a positive effect on entrepreneurial intentions, (3) education had a positive effect on entrepreneurial intentions, and (4) the social environment had a positive effect on entrepreneurial intention